Identification of Salmonella Sp. in Duck Eggs Sold in Larangan Village - Putri, Nadia Auditia; Khusna , Umi Nihayatul; Jaman , Anwar (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2025)
Background: Duck eggs are one of the foodstuffs that are very susceptible to damage caused by microbes. The types of microbes that contaminate eggs are mainly from the Gram-negative bacteria type, including Salmonella. Objectives: The purpose of this study was to determine the salmonella sp bacteria in duck eggs sold in Larangan village Materials and Methods: The examination method used was observation of laboratory tests, isolation methods, and identification of bacteria using biochemical tests. The samples used were duck egg yolks, using Brain Heart Infusion Broth (BHIB) media, Salmonella Shigella Agar (SSA), gram staining, Triple Sugar Iron Agar (TSIA), Simon citrate, and Sulfide Indol Motility (SIM). Results: The results of the research that has been done on BHIB media obtained 6 samples showed bacterial growth, on SSA media 6 duck egg samples showed bacterial colony growth, on gram staining obtained gram-negative and rod-shaped bacteria in 6 samples, on TSIA media obtained positive results on 6 media, simon citrate test showed positive results on 6 media, SIM test on motile test 6 media obtained positive results, on sulfide test 5 media obtained positive results, while indole test 6 media obtained negative results. Conclusions: Based on the results of research on the identification of salmonella sp bacteria in duck eggs sold in Larangan village, Larangan sub-district, Brebes regency, Central Java, it was found that 6 duck egg samples contained salmonella sp bacteria.